2011
DOI: 10.1007/s00401-011-0835-x
|View full text |Cite
|
Sign up to set email alerts
|

Spindle cell oncocytoma of the pituitary gland with follicle-like component: organotypic differentiation to support its origin from folliculo-stellate cells

Abstract: Spindle cell oncocytoma (SCO) is a rare, nonadenomatous tumor originating from the anterior pituitary gland. Composed of fusiform, mitochondrion-rich cells sharing several immunophenotypic and ultrastructural properties with folliculo-stellate cells (FSC), SCO has been proposed to represent a neoplastic counterpart of the latter. To date, however, SCO has failed to meet one criterion commonly used in histological-based taxonomy and diagnostics; that of recapitulating any of FSCs' morphologically defined develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Although typically described as positive in SCO, galectin-3 is generally not useful in the workup of primary sellar neoplasms, as pituicytoma, meningioma, nerve sheath tumors, granular cell tumor, and even metastases have consistently expressed galectin-3 (Rodriguez et al, 2008). The cases in which bcl2 immunohistochemistry has been performed on SCO have largely showed negative expression; however there are two previously reported cases besides our case with immunopositivity for bcl2 (Vajtai et al, 2006;Vajtai, Beck, Kappeler, & Hewer, 2011). …”
Section: Discussionmentioning
confidence: 58%
“…Although typically described as positive in SCO, galectin-3 is generally not useful in the workup of primary sellar neoplasms, as pituicytoma, meningioma, nerve sheath tumors, granular cell tumor, and even metastases have consistently expressed galectin-3 (Rodriguez et al, 2008). The cases in which bcl2 immunohistochemistry has been performed on SCO have largely showed negative expression; however there are two previously reported cases besides our case with immunopositivity for bcl2 (Vajtai et al, 2006;Vajtai, Beck, Kappeler, & Hewer, 2011). …”
Section: Discussionmentioning
confidence: 58%
“…The tumor was diagnosed as a mixed ependymal and oncocytic pituicytoma. Vajtai et al [12] reported another interesting TTF-1 positive sellar tumor showing similar histological features. The tumor was composed of fusiform oncocytic cells with follicle-like cavities that were immunopositive for S100 protein, vimentin, and TTF-1 and negative for GFAP and CAM5.2.…”
Section: Discussionmentioning
confidence: 92%
“…GFAP is variably detected in all of these tumors, but preferentially in pituicytomas. Immunoreactivity for neuronal markers was reported in a few cases of SCO and pituicytoma [4,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that, besides their role as sustentacular cells of the adenohypophysis, folliculo-stellate cells are characterised by a great plasticity and possess the ability to modulate the hypothalamo-hypophyseal-adrenal axis in special conditions [11,12]. In spindle cell oncocytoma, a discussed pathologic entity, which seems to originate from folliculo-stellate cells, tumour cells are positive for S100 but, surprisingly, negative for GFAP [13][14][15]. Unlike spindle cell oncocytomas and adenomas of the anterior hypophysis, the adamantinomatous type of craniopharyngioma exhibits a positive GFAP reaction, while other tumour types appear to be negative for both S100 protein and GFAP but positive for TTF1 [16,17].…”
Section: Introductionmentioning
confidence: 99%